The Influence of Project-Based Learning Model to Improve Students’ Creative Thinking on Colloid Subject (Universitas Negeri Semarang, 2020)
Creative thinking skill plays important roles in developing student’s creativity in solving problems. This study aims at investigating the influence of project-based learning model in improving students’ creative thinking on colloid subject. This study used experimental one group (pretest-posttest) design. 38 students were involved in this study as the samples. According to the analysis results, the N-gain score of the students’ creative thinking skill was 0.72 (high). The analysis showed that project-based learning model gave significant improvement, and the students showed very good response to project-based learning model. Therefore, the model is recommended to be applied in schools.